Microcontrollers from assembly language to C using the PIC24 family - Jones, Bryan A.; Reese, Robert B.; Bruce, J.W (Cengage Learning PTR, 2015)
Covers assembly language, C programming, and hardware interfacing for the Microchip PIC24 family, a microcontroller family from Microchip